2019
DOI: 10.1016/j.ceramint.2019.03.206
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of an innovative zirconia-mullite raw material sintered from andalusite and zircon precursors and an evaluation of its corrosion and thermal shock performance

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…This may be due to the formation of cracks in the This decrease in porosity may be due to the amorphous phase generated during the decomposition of zircon. The formation of this vitreous phase can improve the densification by sintering in liquid phase [10,13,[19][20][21]. It is also likely that the zirconia particles fill the gaps in the microstructure of the material.…”
Section: Microstructural Studymentioning
confidence: 99%
See 2 more Smart Citations
“…This may be due to the formation of cracks in the This decrease in porosity may be due to the amorphous phase generated during the decomposition of zircon. The formation of this vitreous phase can improve the densification by sintering in liquid phase [10,13,[19][20][21]. It is also likely that the zirconia particles fill the gaps in the microstructure of the material.…”
Section: Microstructural Studymentioning
confidence: 99%
“…This decrease can be attributed to M3 having a greater proportion of amorphous phase (Table 2) in its structure, logically reducing the value of E. However, the Young's moduli of M2 and M3 are superior to that of M1 one, even after having been submitted to three thermal shocks (Table 3, Figure 9). It is likely that this is associated with the repetition of the martensitic transformation Q-M (quadratic in monoclinic) which could occur during thermal shocks between temperatures of 750 • C and 500 • C [10,13]. As these samples have a considerable amount of zirconia in their structure, they can more easily block the propagation of the diffuse microcracks network and, therefore, improve their thermal shock performances.…”
Section: Elastic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mullite-ZrO 2 composite materials can be used in different industries, for example, in glass and steel industries due to their suitable physical, thermal, and mechanical properties, and, also, the excellent corrosion resistance against slags due to the high melting temperature of 2715 °C [2,3]. These composite materials possess high fracture toughness, fracture strength, and thermal shock resistance because the zirconia particles distributed homogeneously in the mullite matrix cause improvement of the properties mentioned [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement of society and the development of science and technology, the performance requirements of refractory materials are getting higher and higher. Many researchers have studied and improved the corrosion resistance of refractories [ 2 , 3 , 4 , 5 , 6 ], thermal shock resistance [ 7 , 8 , 9 ], and anti-wear properties [ 10 ]. M. Yoshikawa et al [ 11 ] studied the erosion resistance of MgO-based spinel and Al 2 O 3 -based spinel refractories and found that these two refractories can replace Al 2 O 3 -Cr 2 O 3 refractories with low chromium content and are more suitable for alkali furnaces.…”
Section: Introductionmentioning
confidence: 99%